Employee human resource management values: validation of a new concept and scale - Drouin-Rousseau, Sophie; Fernet, Claude; Austin, Stéphanie; Fabi, Bruno; Morin, Alexandre J. S. (Frontiers in Psychology, 2023)
Purpose. Although human resource management (HRM) practices all seek to support and improve organizational functioning, the value ascribed to various HRM practices differs greatly among employees. Drawing on an exhaustive measure of HRM practices, this study proposed a new conceptualization and measure of HRM values, the HRM Values Scale (HRM-VS). Design/methodology/approach. To examine the psychometric properties of scores obtained on this new measure, we rely on a sample of 979 employees occupying a variety of jobs within various private and public organizations. Findings. Through the comparison of confirmatory factor analysis (CFA) and exploratory structural equation modeling (ESEM) solutions, our results supported a nine-factor structure of participants’ responses to the HRM-VS and the measurement invariance of this solution across male and female employees. Specifically, they support that the HRM-VS items adequately capture core HRM values underlying independent HRM practices. Criterion-related validity was evidenced with respect to employees’ ratings of intrinsic and extrinsic job satisfaction. Research implications. The HRM-VS appears to represent a promising tool for research and intervention seeking to account for individual differences in the relative importance of various HRM practices, in order to devise more effective HRM systems. Practical implications. This new concise but complete measure could help better guide organizations in tailoring their strategic HRM. Originality/value. This study introduces HRM values as a valid concept that characterizes what employees desire or consider to be important in relation to HRM practices.